Oxygen and pCO2 in the Surface Waters of the Atlantic Southern Ocean in 2021–2022 - Natalia A. Orekhova; Sergey K. Konovalov; Alexander A. Polukhin; Anna M. Seliverstova (Water, 2023)
The carbon dioxide concentration in the atmosphere has progressively risen since pre-industrial times. About one-third of the anthropogenically generated CO2 is absorbed by the waters of the World Ocean, whereas the waters of the Southern Ocean take up about 40% of this CO2. The concentrations of oxygen and carbon dioxide dissolved in seawater are sensitive to climate changes, transferring anthropogenic pressures with consequences for the biogeochemical cycles in the World Ocean. The Southern Ocean is a key region for the exchange of oxygen and carbon between the surface water and the atmosphere and for their transfer with cold water masses to the deep layers of the Ocean. In this paper, we discuss the dynamics of the carbon dioxide partial pressure (pCO2) and dissolved oxygen (O2) in the surface waters of the Atlantic Southern Ocean based on data collected during the 87th cruise of the R/V “Academik Mstislav Keldysh”. The study area includes the Bransfield Strait, Antarctic Sound, the Powell Basin, the Weddell, and Scotia Seas. We have analyzed the spatial distribution of pCO2 and oxygen for the areas of transformation of water masses and changes in biogeochemical processes. In the zone of Scotia and Weddell Seas, we have observed an increase in pCO2 and a decrease in oxygen concentrations at the transect from the Weddell Sea at 56° W to the Powell Basin. From the Antarctic Sound to the Bransfield Strait, a decrease in oxygen saturation and an increase in pCO2 has been traced. The surface waters of the Bransfield Strait have revealed the greatest variability of hydrochemical characteristics due to a complex structure of currents and intrusions of different water masses. In general, this area has been characterized by the maximum pCO2, while the surface waters are undersaturated with oxygen. The variability of the AOU/ΔpCO2 (w-a) ratio has revealed a pCO2 oversaturation and an O2 undersaturation in the waters of the Bransfield Strait. It is evidence of active organic carbon decomposition as the major controlling ...